Pengaruh Karakteristik Komite Audit, Keahlian Keuangan Dan Ukuran Perusahaan Terhadap Kemungkinan Kecurangan Laporan Keuangan [The Influence of Audit Committee Characteristics, Financial Expertise, and Company Size toward the Possibility of Financial Report Fraud] - Bambang Leo Handoko; Kinanti Ashari Ramadhani (DeReMa (Development Research of Management): Jurnal Manajemen, 2017)
Related to fraudulent financial statements by PT. Kimia Farma, Indosat, and others, this research looked at fraud committed by companies. The purpose of this research was to determine if the audit committee's independence, the financial expertise of the audit committee, and the size of the company were factors in possible fraudulent financial statements of manufacturing companies listed on the Indonesian Stock Exchange during the period 2013-2015. The possibility of fraudulent financial statements is measured by Beneish M-score. Quantitative research was conducted using an associative methodology and regression analyzing logistics (logistic regression). 82 companies were chosen using purposive sampling technique and secondary data. The results showed that the independence of the audit committee and the size of the company had no effect on the possibility of fraudulent financial statements and the financial expertise of the audit committee had an influence on the possibility of fraudulent of financial statements.BAHASA INDONESIA ABSTRAK:  Terkait kasus kecurangan laporan keuangan yang dilakukan PT.Kimia Farma, Indosat dan lain-lain maka penelitian ini akan mendeteksi kecurangan yang dilakukan perusahaan. Tujuan penelitian ini adalah untuk mengetahui pengaruh komite audit independen, keahlian keuangan komite audit dan ukuran perusahaan terhadap kemungkinan kecurangan laporan keuangan pada perusahaan manufaktur yang terdaftar di Bursa Efek Indonesia periode 2013-2015. Kemungkinan kecurangan laporan keuangan diukur melalui Beneish M-score. Jenis penelitiannya kuantitatif dengan metode penelitian asosaitf dan teknis analisis datanya menggunakan regresi logistic (logistic regression). 82 perusahaan dipilih menggunakan teknik purposive sampling dan menggunakan data sekunder. Hasil penelitian menunjukkan komite audit independen dan ukuran perusahaan tidak berpengaruh pada kemungkinan kecurangan laporan keuangan sedangkan keahlian keuangan komite audit berpengaruh pada kemungkinan kecurangan laporan keuangan.